Economic reform in China and India development experience in a comparative perspective - Chai, C. H.; Roy, K. C. (Kartik Chandra), 1941-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2006)
Recent acceleration of the Indian economic growth rate from 6 to 8 per cent has sparked worldwide speculation that India is about to catch up with China and become another Asian miracle economy. Economic Reform in China and India examines this prospect, reviewing the development strategies pursued by the two countries over the last 50 years in general and exploring recently introduced reform measures in particular.
1. Initial conditions and alternative paths to economic development -- 2. The economic system and its reform -- 3. Agricultural development -- 4. Industrial policy -- 5. Foreign trade and investment -- 6. Saving and investment -- 7. Population and employment -- 8. Growth and human development -- 9. Women's empowerment -- 10. Environment in planned development -- 11. Democratization -- 12. Conclusion and the prospects.
Includes bibliographical references and index.
Keywords: Economic development; China -- Economic conditions -- 2000-; India -- Economic conditions -- 1947-; Electronic books